REPOSISI BUDAYA DALAM MEWUJUDKAN SUSTAINABILITAS PEMBANGUNAN EKONOMI BANGSA - Widayat, Widayat (Jurnal Bestari, 2009)
Culture as a unique characteristic of a nation has capital function in creating sustainability of economic development. In the culture, capital function can be seen from two aspects; as an instrument and constituent. Furthermore, culture contains physical (tangible) and non-physical (intangible) aspects that are useful in building nation's competitive and advantageous competence, as well as a source of national income.